1,3-Di-3-pyridyl-2,3-dihydro-1H-naphth[1,2-e] [1,3]oxazine - Sen, Betuel; Turgut, Zuhal; Pelit, Emel; Aygun, Muhittin (BLACKWELL PUBLISHING, 2008)
In the crystal structure of the title compound, C22H17N3O, the oxazine ring has a half-chair conformation. The dihedral angles between the best least-squares plane through the pyridine rings and the planar part (O-C-C-C-N) of the oxazine ring are 72.14 ( 6) and 35.44 (7)degrees, the smaller angle involving the pyridine ring adjacent to the oxazine O atom. The molecule has two stereogenic centers at the oxazine carbons, RS and SR. The crystal packing reveals that symmetry-related molecules are linked by intermolecular N-H center dot center dot center dot N hydrogen bonds to form chains parallel to the b axis.
Keywords: RING-CHAIN TAUTOMERISM; Crystallography